2010
DOI: 10.1111/j.1365-2966.2010.17351.x
|View full text |Cite
|
Sign up to set email alerts
|

Early-type galaxies in different environments: an H i view

Abstract: We present an analysis of deep Westerbork Synthesis Radio Telescope observations of the neutral hydrogen in 33 nearby early‐type galaxies selected from a representative sample studied earlier at optical wavelengths with the SAURON integral‐field spectrograph. This is the deepest homogeneous set of H i imaging data available for this class of objects. The sample covers both field environments and the Virgo cluster. Our analysis shows that gas accretion plays a role in the evolution of field early‐type galaxies,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
186
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(201 citation statements)
references
References 85 publications
14
186
1
Order By: Relevance
“…The non-negligible presence of chemically-enriched cool gas near LRGs extends the findings of H I gas in nearby elliptical galaxies (e.g., Oosterloo et al 2010) to higher redshifts. These massive, quiescent galaxies provide an ideal laboratory for testing possible physical mechanisms to widely distribute heavy elements away from stars in the absence of starburst outflows.…”
Section: Introductionmentioning
confidence: 80%
“…The non-negligible presence of chemically-enriched cool gas near LRGs extends the findings of H I gas in nearby elliptical galaxies (e.g., Oosterloo et al 2010) to higher redshifts. These massive, quiescent galaxies provide an ideal laboratory for testing possible physical mechanisms to widely distribute heavy elements away from stars in the absence of starburst outflows.…”
Section: Introductionmentioning
confidence: 80%
“…At the same time, accretion of gas from the outer halo of an ETG, induced by interaction, could also be possible. Examining 33 galaxies representative of the SAURON sample Oosterloo et al (2010) detected HI in 2/3 of their field sample, concluding that neutral gas accretion plays a role in the evolution of field ETGs. In a survey of about 100 ATLAS3D galaxies, Serra et al (2009) detected HI in about half of the ETGs located outside Virgo.…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge of the gas content in nearby early-type galaxies (the typical hosts of radio-loud AGN) has increased substantially in recent years. Projects like WSRT-SAURON (Morganti et al 2006;Oosterloo et al 2010a) and ATLAS 3D (Serra et al 2012;Young et al 2011;Davis et al 2013) have studied the properties of H i and molecular gas in nearby early-type galaxies. For example, detailed studies of the H i content of early-type galaxies in the nearby Universe has shown that H i is detected in emission in about 40 percent of early-type galaxies in the field (Serra et al 2012).…”
Section: Introductionmentioning
confidence: 99%